Intuition, reflection, and prosociality: Evidence from a field experiment - Grehl, Sascha; Tutić, Andreas (PloS one, 2022)
Are humans instinctively good or is it only our capacity for reflection that enables us to restrain our selfish traits and behave prosocially? Against the background of dual-process theory, the question of whether people tend to behave prosocially on intuitive grounds has been debated controversially for several years. Central to this debate is the so-called social heuristic hypothesis (SHH), which states that subjects orient their behavior more closely to their deeply ingrained norms and attitudes when the behavior comes about in an intuitive rather than reflective manner. In this paper, we apply the SHH to a novel setting and investigate whether its implications hold true in a non-reactive field experiment, in which subjects are unaware that they are part of a study. We test whether subjects report a misdirected email or try to use the opportunity to reap a monetary benefit. Since all subjects participated six months prior to the field experiment in a lab experiment, we have solid measures of the subjects’ general tendency to behave intuitively and their prosocial attitudes. In addition, participants were asked in a follow-up survey to self-report their intuitiveness at the time of the decision. While we observe a significant and positive effect on prosocial behavior for self-reported intuitiveness (but not for general intuitiveness) in the bivariate analyses, this effect becomes insignificant when controlling for interaction effects with attitudes. In addition, for both forms of intuitiveness, we find a significant and positive interaction effect with subjects’ prosocial attitudes on prosocial behavior. Hence, this study confirms previous findings from laboratory as well as online studies and provides external validity by demonstrating that the SHH applies in a real-life situation.